Management of Recurrent Cervicovaginal Prolapse in a Pregnant Crossbred Jersey Cow - I Assad, Nafis; Khatun, Arjuma; Bhat, Gh Rasool; Sakeena, Sadaf; Naikoo, Mehrajuddin; Malik, Asloob Ahmad; Malik, Faisal Ahmad (The Indian Journal of Animal Reproduction, 2024)
A case of chronic recurrent cervicovaginal prolapse and a tear at ventral commissure of vagina and its management by  Buhner’s suture placed till term using infusion drip set tubing is reported. The recovery was uneventful with delivery of  a live calf at term.
Keywords: Cervicovaginal prolapse; Pregnant; Crossbred cow; Jersey